2016
DOI: 10.5267/j.ijiec.2015.7.003
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization of surface roughness, cutting forces, productivity and Power consumption when turning of Inconel 718

Abstract: Nickel based super alloys are excellent for several applications and mainly in structural components submitted to high temperatures owing to their high strength to weight ratio, good corrosion resistance and metallurgical stability such as in cases of jet engine and gas turbine components. The current work presents the experimental investigations of the cutting parameters effects (cutting speed, depth of cut and feed rate) on the surface roughness, cutting force components, productivity and power consumption d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…RSM can represent the direct and interactive effects of process parameters through the analysis of variance (ANOVA). Moreover, this approach applied in the present work is considered as a procedure to identify a relationship between independent input process parameters and output data (process response), which includes commonly six steps as it is indicated by Gaitonde et al [21] and Tebassi et al [20]: (1) define the independent input variables and the desired output responses, (2) adopt an experimental design plan, (3) perform regression analysis with the required model of RSM as found by Hessainia et al [22] and Zahia et al [23] as shown in Eq. (1).…”
Section: Methods 221 Response Surface Methodology Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…RSM can represent the direct and interactive effects of process parameters through the analysis of variance (ANOVA). Moreover, this approach applied in the present work is considered as a procedure to identify a relationship between independent input process parameters and output data (process response), which includes commonly six steps as it is indicated by Gaitonde et al [21] and Tebassi et al [20]: (1) define the independent input variables and the desired output responses, (2) adopt an experimental design plan, (3) perform regression analysis with the required model of RSM as found by Hessainia et al [22] and Zahia et al [23] as shown in Eq. (1).…”
Section: Methods 221 Response Surface Methodology Approachmentioning
confidence: 99%
“…Response surface methodology is an empirical and widely accepted statistical modeling technique employed for multiple regression analysis using quantitative data obtained from properly designed experiments to solve multivariate equations simultaneously as found by Maran et al [19] and Tebassi et al [20]. RSM approach proceeds with carrying out statistically designed experiments, followed by evaluating the coefficients in a mathematical relationship, the prediction of response and examining the sufficiency of the model.…”
Section: Methods 221 Response Surface Methodology Approachmentioning
confidence: 99%
“…Considering mechanical properties of workpiece, specific shearing energy which is a strong function of feed rate; was the largest at the lowest cutting speed (125 m/min) and reduces subsequently when the cutting speeds increases up to 300 m/min (Pawade et al, 2009). Regarding surface quality and productivity, Yadav et al (2015) and Tebassi et al (2016b) obtained that the most influencing factor on MRR is depth of cut, whereas spindle speed and depth of cut are the most influencing factors on flank wear. In the same way, at low feed rate; the tendency for built-up edge formation, is also higher than at a higher feed, due to an increase in the size of the plastic deformation area at the interface of the tool and workpiece (Zhou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The predicted responses are Ra = 0.30 µm and 8142.14 mm 3 /min for MRR with desirability value of 1.00 as shown in Fig. 13; which presents solution ramps of multi-objective optimization (Tebassi et al, 2016b). …”
Section: Mathematical Modelsmentioning
confidence: 99%
See 1 more Smart Citation